Pharmacokinetics, efficacy and safety of daclatasvir plus asunaprevir in dialysis patients with chronic hepatitis C: pilot study. Issue 11 (27th June 2016) - Kawakami, Y.; Imamura, M.; Ikeda, H.; Suzuki, M.; Arataki, K.; Moriishi, M.; Mori, N.; Kokoroishi, K.; Katamura, Y.; Ezaki, T.; Ueno, T.; Ide, K.; et al.
Summary: The aim of this study was to evaluate the pharmacokinetic profile of daclatasvir (DCV) and asunaprevir (ASV) dual therapy in haemodialysis patients infected with hepatitis C virus (HCV). Eighteen haemodialysis patients and 54 patients with normal renal function were treated with DCV and ASV dual therapy for 24 weeks. We evaluated the pharmacokinetic profiles of DCV and ASV and examined the rate of sustained virological response 12 weeks after the end of treatment (SVR12 ) and incidence of adverse events during treatment of haemodialysis patients infected with chronic HCV genotype 1 infection. To adjust for potential differences in baseline characteristics between haemodialysis patients and patients with normal renal function, we used propensity scores case–control matching methods. Area under the plasma concentration time curve from 0 to 6 h (AUC0–6 h ) of DCV was slightly lower in haemodialysis patients than in patients with normal renal function ( P > 0.6). AUC0–6 h of ASV was significantly lower in haemodialysis patients ( P = 0.012). SVR12 rates were 100% (18/18) for haemodialysis and 96.2% (52/54) for patients with normal renal function. Changes in mean log10 HCV RNA levels and viral response were higher in haemodialysis patients compared to patients with normal renal function. No discontinuations due to adverse events occurred. In conclusion, DCV and ASV dual therapy for HCV infection is effective and safe with similar results in haemodialysis patients compared to patients with normal renal function.